Copper Nanowires: The Role of Cuprous Oxide Seeds in the One‐Pot and Seeded Syntheses of Copper Nanowires (Small 9/2014). Issue 9 (May 2014) - Ye, Shengrong; Rathmell, Aaron R.; Ha, Yoon‐Cheol; Wilson, Adria R.; Wiley, Benjamin J.
<x xml:space="preserve">Abstract</x> On page 1771, B. J. Wiley and co‐workers report that removal of ethylenediamine from a copper nanowire synthesis leads to the rapid formation of Cu2O octahedra. These Cu2O octahedra can be used as seeds in a synthesis to control nanowire aspect ratio. Transparent conducting films are made from nanowires to examine the effect of nanowire aspect ratio on the film performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>